Toradora. Vol. 8 - Takemiya, Yuyuko, 1978-; Eloriaga-Amago, Bambi (Seven Seas Entertainment, LLC, 2018)
When Kitamura bleaches his hair and refuses to run for student council president, it sends Taiga into a flaming rage, and it is not long before she is storming into classrooms and starting fights.